Career Counselling For The Academically Gifted Student - Stewart, John B. (Canadian Journal of Counselling and Psychotherapy, 2007)
This article deals with seven career development and occupational decision-making difficulties experienced by academically gifted students: narrowing the occupational choice, indecision, vocational identity formation, lack of occupational meaningfulness, early occupational choice, pressure from significant others and the need for occupational role models. Each difficulty is discussed with recommendations for counselling interventions. These career development and occupational decision-making difficulties are explained within social learning theory.